A Change in Inflammatory Footprint Precedes Plaque Instability: A Systematic Evaluation of Cellular Aspects of the Adaptive Immune Response in Human Atherosclerosis - van Dijk, R. A.; Duinisveld, A. J. F.; Schaapherder, A. F.; Mulder‐Stapel, A.; Hamming, J. F.; Kuiper, J.; de Boer, O. J.; van der Wal, A. C.; Kolodgie, F. D.; Virmani, R.; Lindeman, J. H. N. (Journal of the American Heart Association, 2015)
Experimental studies characterize adaptive immune response as a critical factor in the progression and complications of atherosclerosis. Yet, it is unclear whether these observations translate to the human situation. This study systematically evaluates cellular components of the adaptive immune response in a biobank of human aortas covering the full spectrum of atherosclerotic disease. A systematic analysis was performed on 114 well-characterized perirenal aortic specimens with immunostaining for T-cell subsets (CD3/4/8/45RA/45RO/FoxP3) and the Th1/non-Th1/Th17 ratio (CD4(+)T-bet(+)/CD4(+)T-bet(-)/CD4(+)/interleukin-17(+) double staining). CD20 and CD138 were used to identify B cells and plasma cells, while B-cell maturation was evaluated by AID/CD21 staining and expression of lymphoid homeostatic CXCL13. Scattered CD4 and CD8 cells with a T memory subtype were found in normal aorta and early, nonprogressive lesions. The total number of T cells increases in progressive atherosclerotic lesions (≈1:5 CD4/CD8 T-cell ratio). A further increase in medial and adventitial T cells is found upon progression to vulnerable lesions.This critical stage is further hallmarked by de novo formation of adventitial lymphoidlike structures containing B cells and plasma cells, a process accompanied by transient expression of CXCL13. A dramatic reduction of T-cell subsets, disappearance of lymphoid structures, and loss of CXCL13 expression characterize postruptured lesions. FoxP3 and Th17 T cells were minimally present throughout the atherosclerotic process. Transient CXCL13 expression, restricted presence of B cells in human atherosclerosis, along with formation of nonfunctional extranodal lymphoid structures in the phase preceding plaque rupture, indicates a "critical" change in the inflammatory footprint before and during plaque destabilization.